Resolution of employment termination disputes in the industrial relations court cocerning works rights specifically in relation - Sunarno, Sunarno; Santoso, M. Iman; Anggaraini, AM Tri; Budiman, Anwar (Indonesian Journal of Multidisciplinary Science, 2024)
This paper examines how future arrangements can enhance legal certainty and foster a sense of justice for workers in Indonesia, thereby positively impacting the overall business environment. The study provides a conceptual framework for evaluating and proposing legal and policy reforms that can ensure justice for the workers. The research serves as a foundation for policymakers to design and implement effective labor laws that promote fairness and equity. The findings of this study have practical implications for businesses operating in Indonesia. This research contributes to the understanding of the intersections between legal frameworks, workers' rights, and business practices in the Indonesian context. The results of this research provide valuable guidance for stakeholders, including government agencies, businesses, and labor organizations, on the importance of creating arrangements that support worker justice.